Risk management committee, independent commissioner, and audit fee: An update - Nadia Klarita Rahayu; Iman Harymawan; Wulandari Fitri Ekasari; John Nowland (Cogent Economics & Finance, 2021)
We investigate whether the risk management committee and independent commissioner contribute to the audit fee. We use 720 observations from Indonesian listed companies for 2015-2018. We use ordinary least square analysis to address our hypotheses. The result shows that the proportion of independent commissioners weakens the relationship between RMC and audit fees. Our study proved that the existence of a risk management committee would lead to a higher demand for audit coverage. As a result, the audit fee increased. RMC may demand high-quality external assurance, but it may be ignored because the independent commissioner has more authority than RMC. In addition, we also used coarsened exact matching with a consistent result as the OLS. These findings provide evidence for policymakers on the relationship between audit fees and risk management committees.
Keywords: G32; G34; 330; audit fee; independent commissioner; Risk management committee